Die Lohnsteuer- und die Sozialabgabenbelastung ausgewählter Arbeitnehmerhaushalte in Deutschland 2013-2017 - Alfred Boss (Kiel Institute for the World Economy (IfW), 2014)
– The tax burden of typical wage income earners in Germany is analyzed. It turns out that the overall tax rate (wage income tax, solidarity surcharge, contributions to social security) for selected singles will go up in the period 2013-2017 if the tax rules will not be changed. The main reason is the progressivity of the income tax rate structure. In order to avoid stronger disincentives to work, the income tax rate structure should be indexed according to the development of the average wage income.
Keywords: H24; H25; 330; wage income tax; tax bracket creep; contributions to social security